Aloe Vera-Based Concrete Superplasticizer for Enhanced Consolidation with Limestone Calcined Clay Cement - Andrew Onderi Nyabuto; Silvester Ochieng Abuodha; John Nyiro Mwero; Lenka Scheinherrová; Joseph Mwiti Marangu (Applied Sciences, 2023)
Self-consolidating concrete (SCC) is renowned for its outstanding workability and ability to seamlessly flow into intricate structures with minimal vibrations, achieved through the incorporation of chemical admixtures. This study pioneers an innovative approach by exploring the use of the cost-effective and readily available plant extract aloe vera mucilage (AVM) as a bio-admixture for SCC. The primary objective is to assess the impact of AVM on SCC formulations, including those comprising ordinary Portland cement (OPC) and blended cement LC3 (clinker 50%, calcined waste clay 30%, limestone 15%, gypsum 5%). AVM is applied at varying dosages at up to 10%. Findings reveal that LC3 exhibits lower consistency, reduced slump values, and extended initial and final setting times compared to OPC. With increasing plasticizer dosage, V-funnel and L-box values decrease. Notably, OPC samples with both plasticizers outperform LC3 in compressive strength at 7, 14, and 28 days. Significantly, a 2.5% AVM dosage demonstrates enhanced compressive strength in both OPC and LC3 samples. In summary, this research positions AVM as an innovative and comparable alternative to commercial plasticizers, contributing to reduced yield stress and increased slump flow in SCC.